2022
DOI: 10.21203/rs.3.rs-1905853/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bivariate binary logistic regression analysis on undernutrition and anemia among under-five children in Rwanda; evidence from 2019/20 Rwanda demographic health survey

Abstract: Background: In low and middle-income countries such as Rwanda, undernutrition and anemia were major causes of death and morbidity among children under the age of five. Thus, this study aims to conduct a bivariate binary logistic regression model by accounting for the possible dependency of childhood undernutrition and anemia. Methods:The data came from the DHS program's measurement. A total of 3,206 under-five children were involved in this study. A single composite index measure was calculated for stunting, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A preprint has previously been published [17]. However, the discovery has yet to be published in another journal.…”
Section: Description Of Preprintmentioning
confidence: 99%
See 1 more Smart Citation
“…A preprint has previously been published [17]. However, the discovery has yet to be published in another journal.…”
Section: Description Of Preprintmentioning
confidence: 99%
“…A study done in Ethiopia found that the common and significant predictors of stunting and underweight included the child's age, anemia level, and type of birth. A child's birth size was strongly linked to a higher risk of stunting, underweight, and wasting in children under the age of five [17]. Significant correlations have been shown between undernutrition and region, fever in the previous two weeks, birth type, mother's BMI, parents' education level, wealth index, family size, number of children, and maternal age [13][14][15].…”
Section: Introductionmentioning
confidence: 99%